Hybridity in Jhumpa Lahiri's a Temporary Matter - Yulistiyanti Yulistiyanti; Agnes Widyaningrum; Endang Yuliani Rahayu; Katharina Rustipa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aims to reveal hybridity and liminality in Jhumpa Lahiri's short story entitled A Temporary Matter. This research is a qualitative research with a postcolonial approach. The theory used in this research is postcolonialism theory by Homi K. Bhabha. The methods applied in this study include data collection methods and data analysis methods. The data obtained were taken from the speech of the characters and the narrator in the short story A Temporary Matter. Bhabha in The Location of Culture (1994) discusses hybridity in society during the post-colonial era and is applied to diaspora literature. Hybridity is related to human culture and identity. Culture and identity are formed dynamically, they experience development, progress, and decline according to conditions and circumstances. Diaspora literature is produced from the writings of people living outside the country and/or writings that contain diaspora experiences. In the process of hybridity, there is a gap between the two cultures. The gap is called liminality in which there is repression of the (colonial) past that is not revealed. One of the writers included into the category of diaspora writers is Jhumpa Lahiri. In A Temporary Matter, she shows the hybridity experienced by the two main characters of Indian descent living in the United States. They were husband and wife; Shukumar and Shoba. They experienced cultural adaptation to cultures outside India. In their lives, cultural mixing occurs. This mixture is seen in the food, clothing, and language they use. Between these mixtures, several gaps fill the transition. This is found in the main character's utterances.